2019
DOI: 10.1071/an17516
|View full text |Cite
|
Sign up to set email alerts
|

Farmed red deer home range, habitat use and daily movement patterns in a Southland, New Zealand, tussock grassland over calving and lactation

Abstract: Considerable expansion of red deer farming has occurred in the South Island high country of New Zealand. On these farms, breeding hinds are usually continuously grazed (set-stocked) at low population densities in large highly modified native-tussock grassland paddocks during their calving and lactation seasons. The present study determined how these hinds use the tussock grassland over this critical period, identifying the most essential resources for them and also some potential long-term consequences of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(58 reference statements)
1
1
0
Order By: Relevance
“…This research proved the central hypothesis of consistent variation in foraging behaviour among sire lines but did not prove the hypothesis that behaviour influences liveweight gain. All animals on both treatments experienced dawn and dusk peaks in activity, as previously demonstrated in red deer (Hester et al 1996;Pépin et al 2006;Ensing et al 2014;Wall et al 2019). However, the diurnal pattern of activity appears to be different for the two groups, with the kale group having an extended morning activity period, followed by a distinct lack of activity until the evening period.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This research proved the central hypothesis of consistent variation in foraging behaviour among sire lines but did not prove the hypothesis that behaviour influences liveweight gain. All animals on both treatments experienced dawn and dusk peaks in activity, as previously demonstrated in red deer (Hester et al 1996;Pépin et al 2006;Ensing et al 2014;Wall et al 2019). However, the diurnal pattern of activity appears to be different for the two groups, with the kale group having an extended morning activity period, followed by a distinct lack of activity until the evening period.…”
Section: Discussionsupporting
confidence: 65%
“…Several genetic markers have been found that explained up to 24% of the phenotypic variation in terrain use by cattle (Bailey et al 2015) and foraging behaviour has consistently been shown to differ among breeds within a species (Bailey et al 2001;Russell et al 2010;Aharoni et al 2013;Dolev et al 2014;Nyamuryekung'e et al 2021) and among individuals within a population of the same breed (Michelena et al 2009;Sibbald et al 2009;di Virgilio and Morales 2016). The variation in foraging behaviour in red deer has not been investigated in any detail; however, Wall et al (2019) demonstrated that different individuals utilised different vegetation zones within a large herd of farmed red deer, indicating that variation in resource utilisation does occur.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic factors (referenced by 75 studies) are further categorised to include stocking rate, stocking density, grazing intensity, grazing system, livestock weights, mowing, soil and fire management, land use, pasture treatment (i.e., fertilizer, herbicide, nitrogen, etc.) and irrigation [2,7,49,65,66,[80][81][82][83][84][85][86][87][88][89][90]. These variables are quantified through field measurements (and/or ancillary data) and correlated against remote sensing data [50,70].…”
Section: Remotely Sensed Environmental Parameters Applied To Pasture ...mentioning
confidence: 99%